1994
DOI: 10.1139/o94-044
|View full text |Cite
|
Sign up to set email alerts
|

Substitutions for Gly-794 show that binding interactions are important determinants of the catalytic action of β-galactosidase (Escherichia coli)

Abstract: Substitutions of Gly-794 (beta-galactosidase) with Asp, Asn, Glu, and Lys caused decreased binding of substrates and inhibition by substrate analogs, while inhibition by planar and positively charged galactose analogs increased relative to the binding of substrates and the inhibition by substrate analogs. There was a correlation of the relative inhibition with the size of the substituted residue but no relationship to the presence or absence of a negative charge, and as the relative inhibition by the planar an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(26 reference statements)
2
7
0
Order By: Relevance
“…The activity was not increased with all substrates-only those for which the first catalytic step (galactosylation) was rate determining. Further studies 57 showed that b-galactosidases with several different substitutions for Gly794 had similar properties. The structure of the enzyme 8 revealed that Gly794 is a ''hinge'' at one end of a loop near to the active site [ Fig.…”
Section: Overview Of the Enzymatic Reactionmentioning
confidence: 98%
“…The activity was not increased with all substrates-only those for which the first catalytic step (galactosylation) was rate determining. Further studies 57 showed that b-galactosidases with several different substitutions for Gly794 had similar properties. The structure of the enzyme 8 revealed that Gly794 is a ''hinge'' at one end of a loop near to the active site [ Fig.…”
Section: Overview Of the Enzymatic Reactionmentioning
confidence: 98%
“…This may be due to the larger size of serine/threonine derivatives leading to better interactions with the amino acid residues found in the large acceptor-binding site of the enzyme as compared to the smaller monosaccharides. However, these binding affinities were weaker than the experimental binding affinities of ONPG (−8.1~−8.2 kcal/mol) at the degalactosylation step [ 22 , 23 ]. This slightly weaker binding affinity of E. coli β-galactosidase towards its acceptors may also reflect the importance of the thermodynamic equilibrium between the transgalactosylation and hydrolysis reaction.…”
Section: Resultsmentioning
confidence: 67%
“…In M278VP1, the acceptor site is a protruding loop extending towards the active site of the partner monomer, forming the activating interface between the components of the dimer [6]. In JX795A, the receiving, solvent‐exposed loop embraces the Gly 794 , an amino acid residue involved in substrate binding [28]. The atomic distances between each insertion site and both active sites in the corresponding dimer are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%